Pucciniastrum minimum is the causal agent of blueberry leaf rust on different Vaccinium species in Hawke’s Bay, New Zealand - Chen X; Mesarich CH; Kerckhoffs H; Hutchins D; Sofkova-Bobcheva S (Springer Nature on behalf of the Australasian Plant Pathology Society Inc, 2023)
Blueberry leaf rust has become a prevalent disease in New Zealand blueberry production. To identify the pathogen responsible for this disease in the Hawke’s Bay region of New Zealand, leaves showing signs or symptoms of rust infection were collected from three blueberry cultivars (‘Centra Blue’ [Rabbiteye], ‘Georgia Dawn’ [Southern Highbush] and ‘Nui’ [Northern Highbush]) and the pathogen subjected to morphological characterization using both scanning electron and bright-field microscopy. Meanwhile, genomic DNA was extracted from urediniospores of infected leaves collected from cultivar ‘Rahi’ (Rabbiteye) and the Internal Transcribed Spacer (ITS) region was sequenced and compared to the corresponding nucleotide sequence of known rust pathogens. Results from both experiments indicated that Pucciniastrum minimum (syn. Thekopsora minima) was the causal agent of blueberry leaf rust disease in Hawke’s Bay. Next, the level of disease caused by P. minimum was quantified on 23 blueberry cultivars in this region during the 2019 blueberry production season. Here, a total of 20 leaves selected from each cultivar were continually monitored, and the lesion area was calculated using ImageJ based on images taken in the field. Based on this analysis, all leaves were found to be infected by the rust pathogen. However, disease intensity, as a function of the ‘area under the disease progress curve’ (AUDPC) value, was found to be different. This suggests that certain cultivars display a lower disease intensity during the harvest season. Further field assessment covering a whole growing cycle will give a better understanding about blueberry leaf rust infection on these cultivars.
Keywords: Pucciniastrum minimum (syn. Thekopsora minima); Blueberry leaf rust; Vaccinium spp; Blueberry; Internal transcribed spacer (ITS) region; Area under the disease progress curve (AUDPC); ImageJ